Perception of the incidence of the contents of community radios in the framework of sustainability and human development: case analysis in Ecuador - García Chaguay, Maryuri (2022)
The objective of this research is to determine the perception of the population regarding the contribution of the community radios of the Guaranda canton, Salinas parish, for the construction of sustainability and human development at the parish level, taking as a sample the community radio Salinerito during the year 2017. The research was carried out framed in a qualitative and quantitative approach with participatory methods and techniques, for the work with the audiences from the focus groups and the application of questionnaires, with descriptive character and based on the critical analysis of the content and communication strategies, used by the radio under study. All this allowed for a comparative analysis between community and private radio stations, as premises to determine whether community media have a greater or lesser impact on human development and sustainability (understand a scaffolding that includes the social, economic, political and cultural) from the messages and content broadcast, compared to private radios. As a result, it is considered a proposal of guidelines that can be considered by community radio stations for the promotion of human development and sustainability taking into account the reality of each territory.